Development of Instruments to Detect Disaster Risk in Children Under Five - Sumasto, Hery; Wisnu, Nurwening Tyas; Surtinah, N. (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
The research that has been conducted is aimed to develop disaster risk instruments for children under five. So that can do disaster mitigation, reduce the risk of disaster in children under five, through awareness based on community empowerment.Variables that have been shown to affect disaster risk: the level of threat, vulnerability, and community capacity. These three factors need to be developed specifically in order to be used to assess the level of disaster risks for toddlers. Development of the instrument has been done through 4 stages: 1) conducted preliminary study 2) developed the instrument, 3) conducted data analysis and 4) given the recommendation of the research results. Of the 32 items of disaster risk instrument items, 2 invalid items have been discarded. Of 30 valid instrument items, all significant values ââhave been indicated> 0.700, all instrument items accepted.  Keywords: Disaster risk, Instruments, Toddlers